Tubulocystic Carcinoma of the Kidney With Poorly Differentiated Foci: A Frequent Morphologic Pattern of Fumarate Hydratase-deficient Renal Cell Carcinoma. (November 2016) - Smith, Steven C.; Trpkov, Kiril; Chen, Ying-Bei; Mehra, Rohit; Sirohi, Deepika; Ohe, Chisato; Cani, Andi K.; Hovelson, Daniel H.; Omata, Kei; McHugh, Jonathan B.; Jochum, Wolfram; Colecchia, Maurizio; et al.
Abstract : An emerging group of high-grade renal cell carcinomas (RCCs), particularly carcinomas arising in the hereditary leiomyomatosis renal cell carcinoma syndrome (HLRCC), show fumarate hydratase ( FH ) gene mutation and loss of function. On the basis of similar cytomorphology and clinicopathologic features between these tumors and cases described as tubulocystic carcinomas with poorly differentiated foci (TC-PD) of infiltrative adenocarcinoma, we hypothesized a relationship between these entities. First, 29 RCCs with morphology of TC-PD were identified retrospectively and assessed for FH expression and aberrant succination (2SC) by immunohistochemistry (IHC), with targeted next-generation sequencing of 409 genes—including FH —performed on a subset. The 29 TC-PD RCCs included 21 males and 8 females, aged 16 to 86 years (median, 46), with tumors measuring 3 to 21 cm (median, 9) arising in the right (n=16) and left (n=13) kidneys. Family history or stigmata of HLRCC were identifiable only retrospectively in 3 (12%). These tumors were aggressive, with 79% showing perinephric extension, nodal involvement in 41%, and metastasis in 86%. Of these, 16 (55%) demonstrated loss of FH by IHC (14/14 with positive 2SC). In contrast, 5 (17%) showed a wild-type immunoprofile of FH+/2SC−. An intriguing group of 8 (28%) showed variable FH± positivity, but with strong/diffuse 2SC+. Next-generation sequencing revealed 8 cases with FH mutations, including 5 FH−/2SC+ and 3 FH±/2SC+ cases, but none in FH+/2SC− cases. Secondly, we retrospectively reviewed the morphology of 2 well-characterized cohorts of RCCs with FH-deficiency determined by IHC or sequencing (n=23 and n=9), unselected for TC-PD pattern, identifying the TC-PD morphology in 10 (31%). We conclude that RCCs with TC-PD morphology are enriched for FH deficiency, and we recommend additional workup, including referral to genetic counseling, for prospective cases. In addition, based on these and other observations, we propose the term "FH-deficient RCC" as a provisional term for tumors with a combination of suggestive morphology and immunophenotype but where genetic confirmation is unavailable upon diagnosis. This term will serve as a provisional nomenclature that will enable triage of individual cases for genetic counseling and testing, while designating these cases for prospective studies of their relationship to HLRCC. Abstract : Supplemental Digital Content is available in the text.